(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Metastatic tumor in oral region is uncommon and may occur in the oral soft tissues or in the Jaw bone. Because of their rarity, metastasis in oral cavity are challenging to diagnose and treat. Oral metastasis is associated with poor prognosis. This case report is of a 45 year old female with a small pedunculated swelling on the left side of the hard palate in the molar region for 30 days. Incisional biopsy revealed metastatic leiomyosarcoma with possible primaries in the uterus. Metastasis in the right lung and liver was also diagnosed. Palliative chemotherapy was started but the patient died after two weeks of diagnosis after receiving the first cycle of chemotherapy. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7954 (J Bangladesh Coll Phys Surg 2011; 29: 96-98)